Lexicographic Study of Socio-Economic Terms in English and Uzbek - Farkhadova Nasiba Sukhrob Qizi (Researchparks Publishing, 2021)
This article provides a structural-semantic and lexicographical study of sociological words in the socio-economic sphere and their broad interpretation.